The role of difficulty and gender in numbers, algebra, geometry and mathematics achievement - Rabab’h, Belal Sadiq Hamed; Veloo, Arsaythamby; Perumal, Selvan (2015)
This study aims to identify the role of difficulty and gender in numbers, algebra, geometry and mathematics achievement among secondary schools students in Jordan.The respondent of the study were 337 students from eight public secondary school in Alkoura district by using stratified random sampling.The study comprised of 179 (53%) males and 158 (47%) females students.The mathematics test comprises of 30 items which has eight items for numbers, 14 items for algebra and eight items for geometry.Based on difficulties among male and female students, the findings showed that item 4 (fractions – 0.34) was most difficult for male students and item 6 (square roots – 0.39) for females in numbers.For the algebra, item 11 (inequality – 0.23) was most difficult for male students and item 6 (algebraic expressions – 0.35) for female students.In geometry, item 3 (reflection – 0.34) was most difficult for male students and item 8 (volume – 0.33) for female students.Based on gender differences, female students showed higher achievement in numbers and algebra compare to male students.On the other hand, there was no differences between male and female students achievement in geometry test.This study suggest that teachers need to give more attention on numbers and algebra when teaching mathematics.